Early Neolithic Culture of Baraba Forest Steppe: issues and features - Vyacheslav I. Molodin (Археология евразийских степей)
In October 2024, scientific community celebrates the 70th anniversary of the prominent scientist and science organizer A.A. Vybornov. The issues of Neolithic period are of particular importance in his work, so the issues of Western Siberian Early Neolithic are of undoubted interest to Aleksandr Alekseevich. The Baraba Early Neolithic culture has been discovered recently, but it attracts the constant attention of specialists. This work is dedicated to certain cultural issues that are under development. The obtained series of radiocarbon dates allows the authors to date the culture within the end of the VIII – beginning of the VI millennium BC, and its periodization is currently being developed. A special feature of the culture is the peculiar technology and morphology of flat-bottomed pottery. The set of stone artefacts is characterized by a blade technique of production, rooted in the Upper Paleolithic period. The Baraba culture is characterized by the widespread use of bone, from which products characteristic exclusively for this culture were made, and insert tools. A feature of the culture is the presence of special pits for fish fermentation in settlements, containing ritual offerings in the form of various animals or their parts. The culture appears to be autochthonous, but its western and southwestern relations are clearly recorded.